2023
DOI: 10.1021/acscatal.3c01053
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Mechanistic Details for the Selective Deoxygenation of Carboxylic Acids over Dynamic MoO3 Catalysts

Laura A. Gomez,
Caleb Q. Bavlnka,
Tianhao E. Zhang
et al.

Abstract: The selective activation of renewable carboxylic acids could enable the formation of a variety of highly valuable renewable products, including surfactants, valuable dienes, and renewable hydrogen carriers. A kinetic study is performed to enhance understanding of the selective deoxygenation of carboxylic acid on promoted MoO 3 at mild temperatures. Although several studies indicate that deoxygenation of oxygenated biomass-derived compounds on MoO 3 occurs via a reverse Mars−van Krevelen mechanism, this study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(129 reference statements)
1
0
0
Order By: Relevance
“…By splitting the HDO rate into individual values for the primary propylene and propane products, nearly indistinguishable acetone dependencies of −0.22 ± 0.11 and −0.16 ± 0.13, respectively, were observed. This negative order for the deoxygenation pathway agrees with recent reports of a −0.22 reaction order for the partial deoxygenation of pentanoic acid to pentanal over bulk MoO 3 for similar partial pressure ranges. , Notably, these observed negative orders for aliphatic molecules on MoO 3 are in contrast with the kinetics previously observed for anisole and phenol with MoO 3 /ZrO 2 , as well as 2-propanol and m -cresol on oxygen-modified MoC 2 . ,, As the reaction temperature increased to 380 °C, the acetone order for HDO and aldol condensation increased to 0.02 ± 0.06 and 1.07 ± 0.04 over the same pressure range, indicating a shift in the equilibrium of the most abundant reactive intermediate(s) (MARI) on the molybdenum oxide surface. The consistently observed order difference of ∼1 for the two reactions under multiple conditions indicated that the pathways compete for the same surface sites.…”
Section: Resultssupporting
confidence: 90%
“…By splitting the HDO rate into individual values for the primary propylene and propane products, nearly indistinguishable acetone dependencies of −0.22 ± 0.11 and −0.16 ± 0.13, respectively, were observed. This negative order for the deoxygenation pathway agrees with recent reports of a −0.22 reaction order for the partial deoxygenation of pentanoic acid to pentanal over bulk MoO 3 for similar partial pressure ranges. , Notably, these observed negative orders for aliphatic molecules on MoO 3 are in contrast with the kinetics previously observed for anisole and phenol with MoO 3 /ZrO 2 , as well as 2-propanol and m -cresol on oxygen-modified MoC 2 . ,, As the reaction temperature increased to 380 °C, the acetone order for HDO and aldol condensation increased to 0.02 ± 0.06 and 1.07 ± 0.04 over the same pressure range, indicating a shift in the equilibrium of the most abundant reactive intermediate(s) (MARI) on the molybdenum oxide surface. The consistently observed order difference of ∼1 for the two reactions under multiple conditions indicated that the pathways compete for the same surface sites.…”
Section: Resultssupporting
confidence: 90%